Perencanaan Bangunan Pengolahan Lumpur Studi Kasus: Perumda Air Minum Kota Padang (IPA Lubuk Paraku) - Noor Azizah, Rifka; Mardiamon, Ressy; Fajar, Mutiara (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2024)
Water Treatment Plants (WTP) in the process will produce mud which can cause shallowing of rivers due to the settling of the mud. Sludge deposition can occur if the sludge is not treated before discharged into water bodies. Based on PP no. 122 of 2015, drinking water processing production units should be equipped with residual sludge processing units from processing raw water into drinking water. Therefore, the aim of this planning is to plan a sludge processing unit at the Lubuk Paraku WTP of the Padang City Perumda Air Minum. Before planning a sludge processing unit, primary and secondary data will be collected to be used. Primary data was obtained from testing the characteristics of raw water produced based on the parameters pH, turbidity, PAC coagulant dosage and secondary data from companies including HSPK Padang City in 2022. Samples were taken using the grab sampling method, and the selection of alternative sludge processing was carried out using the Decision Analysis method. Matrix. The research results show data that the maximum mass and volume of sludge produced is 14,132.35 kg/day and 333.01 m3/day. The chosen sludge processing unit is a gravity thickener unit with a diameter of 8 m and a height of 6.2 m and a sludge drying bed unit with a length of 28 m, a width of 7 m and a height of 1.33 m. Each building is designed to have 3 units. The planned cost budget used in building the Lubuk Paraku IPA sludge processing installation for Perumda Air Minum Padang City is IDR 692,500,000,-.